Influence of Organic-Inorganic Interaction on Nutrient Use Efficiency and Sugarcane Yield in Calcareous Soils of the Indo-Gangetic Plains, India - Sinha, Sanjeew Kumar; Kumar, Ajeet; Kumar, Brajesh; Kumari, Amrita; Singh, A. K. (Current Research Progress in Agricultural Sciences Vol. 3, 2024)
The current study aims to evaluate integrated nutrient management on cane production and nutrient use efficiency of applied nitrogen, phosphorous, and potassium in sugarcane in terms of agronomic efficiency and physiological use efficiency. Enhancing nutrient use efficiency beyond the typical 50% threshold is crucial for improving sugarcane production and juice quality, while also reducing dependency on synthetic fertilizers and mitigating environmental impact. Nutrient use efficiency (NUE) measures how well plants can absorb and use nutrients to produce their highest possible yields. Thus, the NUE idea encompasses three crucial processes in plants: nutrient absorption, assimilation, and utilisation. To tackle this challenge, a field experiment was conducted at the Kalyanpur research farm, Dr. Rajendra Prasad Central Agricultural University, Pusa, Bihar. Using a randomized block design with three replications, the experiment involved the sugarcane variety CoP-112. Although the treatments showed no significant impact on germination percentage, plant height, cane length, diameter, and individual cane weight, the combination of the recommended dose of fertilizers (RDF) with vermicompost and biofertilizer (Azotobacter + PSB) at a rate of 4 kg/ha resulted in the highest millable cane (125.4×103/ha) and cane yield (94.0 t/ha). This combination led to increases of 78% and 24% over the sole prescribed dose of fertilizer and the absolute control, respectively. No significant differences were observed in juice quality among the treatments. The highest agronomic use efficiency was recorded in plots treated with RDF + vermicompost + Azotobacter + PSB, showing a 75% improvement over plots receiving only the recommended dose of fertilizer. These findings highlight the effectiveness of integrated nutrient management as the optimal strategy for promoting sustainable sugarcane production. The study demonstrated the effectiveness of integrating vermicompost and biofertilizer (Azotobacter + PSB) with the recommended dose of fertilizers for enhancing sugarcane yield and nutrient utilization efficiency.